2020
DOI: 10.3390/pr8091043
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Polymer Extrusion Die Based on Response Surface Method

Abstract: A coupled surface response optimization method with a three-dimensional finite volume method is adopted in this study to identify five independent geometric variables of the die interior that provides a design with the lowest velocity variance at the exit of the coat-hanger extrusion die. Two of these five geometric variables represent the manifold dimension while the other three variables represent the die profile. In this method, B-spline fitting with four points was used to represent the die profile. A comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The variations observed in the solid bed profile are in good agreement with previous single screw literature data, showing that increasing the volumetric flow rate results in an increase of the solid fraction at the same position of the screw length. These observations have been attributed to a shorter time to heat the polymer if higher flow rates are employed [25]. A different study from Lewandowski [57] observed the opposite effect for an intermeshing counter-rotating twin-screw extruder.…”
Section: Effect Of Volumetric Feeding Ratementioning
confidence: 97%
See 2 more Smart Citations
“…The variations observed in the solid bed profile are in good agreement with previous single screw literature data, showing that increasing the volumetric flow rate results in an increase of the solid fraction at the same position of the screw length. These observations have been attributed to a shorter time to heat the polymer if higher flow rates are employed [25]. A different study from Lewandowski [57] observed the opposite effect for an intermeshing counter-rotating twin-screw extruder.…”
Section: Effect Of Volumetric Feeding Ratementioning
confidence: 97%
“…It allows bypassing multiple manufacturing steps such as the filament extrusion before the AM process, relieving the material to one extrusion cycle and leading to less degradation. Its versatility and design simplicity make SSE one of the essential equipment tools for the bulk polymer processing industry [22][23][24][25][26]. Most SSEs are fed by a granular solid polymer, which is melted or plasticized in the screw channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental measurements of polymeric liquids (solution and melt) are routinely carried out to obtain the necessary data on their rheological properties. Then, various numerical methods were used to find a suitable set of parameters for the rheology model to facilitate efficient flow simulations [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that polypropylene can be used to produce low-cost, lightweight, transparent, and flexible thin sheets and films for a variety of applications in industries [1]. The key component in the production of these sheets and films is the extrusion die designs [2,3]. Flow distribution channels in the extrusion dies should be designed in such a way to assure uniform fluid velocity, pressure, temperature in the outlets with uniform thickness [4,5].…”
Section: Introductionmentioning
confidence: 99%